Characteristics of Carbapenem-Resistant Enterobacteriaceae in Ready-to-Eat Vegetables in China - Liu, Bao-Tao; Zhang, Xiao-Yan; Wan, Shu-Wei; Hao, Jun-Jie; Jiang, Rui-De; Song, Feng-Jing (Frontiers in Microbiology, 2018)
Vegetables harboring bacteria resistant to antibiotics are a growing food safety issue. However, data concerning carbapenem-resistant Enterobacteriaceae (CRE) in ready-to-eat fresh vegetables is still rare. In this study, 411 vegetable samples from 36 supermarkets or farmer’s markets in 18 cities in China, were analyzed for CRE. Carbapenemase-encoding genes and other resistance genes were analyzed among the CRE isolates. Plasmids carrying carbapenemase genes were studied by conjugation, replicon typing, S1-PFGE southern blot, restriction fragment length polymorphism (RFLP) and sequencing. CRE isolates were also analyzed by pulsed-field gel electrophoresis (PFGE). Ten vegetable samples yielded one or more CRE isolates. The highest detection rate of CRE (14.3%, 4/28) was found in curly endive. Twelve CRE isolates were obtained and all showed multidrug resistance: Escherichia coli, 5; Citrobacter freundii, 5; and Klebsiella pneumoniae, 2. All E. coli and C. freundii carried blaNDM, while K. pneumoniae harbored blaKPC-2. Notably, E. coli with blaNDM and ST23 hypervirulent Klebsiella pneumoniae (hvKP) carrying blaKPC-2 were found in the same cucumber sample and clonal spread of E. coli, C. freundii and K. pneumoniae isolates were all observed between vegetable types and/or cities. IncX3 plasmids carrying blaNDM from E. coli and C. freundii showed identical or highly similar RFLP patterns, and the sequenced IncX3 plasmid from cucumber was also identical or highly similar (99%) to the IncX3 plasmids from clinical patients reported in other countries, while blaKPC-2 in K. pneumoniae was mediated by similar F35:A-:B1 plasmids. Our results suggest that both clonal expansion and horizontal transmission of IncX3- or F35:A-:B1-type plasmids may mediate the spread of CRE in ready-to-eat vegetables in China. The presence of CRE in ready-to-eat vegetables is alarming and constitutes a food safety issue. To our knowledge, this is the first report of either the C. freundii carrying blaNDM, or K. pneumoniae harboring blaKPC-2 in vegetables. This is also the first report of ST23 carbapenem-resistant hvKP strain in vegetables.